Clinical significance of abnormal electrocardiographic patterns in trained athletes - Pelliccia, A.; Maron, B. J.; Culasso, F.; Di Paolo, F. M.; Spataro, A.; Biffi, A.; Caselli, G.; Piovano, P. (Circulation, 2000)
BACKGROUND-The prevalence, clinical significance, and determinants of abnormal ECG patterns in trained athletes remain largely unresolved. METHODS AND RESULTS-We compared ECG patterns with cardiac morphology (as assessed by echocardiography) in 1005 consecutive athletes (aged 24+/-6 years; 75% male) who were participating in 38 sporting disciplines. ECG patterns were distinctly abnormal in 145 athletes (14%), mildly abnormal in 257 (26%), and normal or with minor alterations in 603 (60%). Structural cardiovascular abnormalities were identified in only 53 athletes (5%). Larger cardiac dimensions were associated with abnormal ECG patterns: left ventricular end-diastolic cavity dimensions were 56. 0+/-5.6, 55.4+/-5.7, and 53.7+/-5.7 mm (P<0.001) and maximum wall thicknesses were 10.1+/-1.4, 9.8+/-1.3, and 9.3+/-1.4 mm (P<0.001) in distinctly abnormal, mildly abnormal, and normal ECGs, respectively. Abnormal ECGs were also most associated with male sex, younger age (<20 years), and endurance sports (cycling, rowing/canoeing, and cross-country skiing). A subset of athletes (5% of the 1005) showed particularly abnormal or bizarre ECG patterns, but no evidence of structural cardiovascular abnormalities or an increase in cardiac dimensions. CONCLUSIONS-Most athletes (60%) in this large cohort had ECGs that were completely normal or showed only minor alterations. A variety of abnormal ECG patterns occurred in 40%; this was usually indicative of physiological cardiac remodeling. A small but important subgroup of athletes without cardiac morphological changes showed striking ECG abnormalities that suggested cardiovascular disease; however, these changes were likely an innocent consequence of long-term, intense athletic training and, therefore, another component of athlete heart syndrome. Such false-positive ECGs represent a potential limitation to routine ECG testing as part of preparticipation screening. Circulation 2000 Jul 18;102(3):278-84